Penyuluhan Kawasan Rumah Tangga Tanpa Asap Rokok Bagi Kelompok Ibu-Ibu PKK Rw 01 Kelurahan Tlogomas Kota Malang - Wahyu Hidayat R; Firasti Agung Nugrahening Sumadi; Rahmad Hidayat (Program Studi Ekonomi Pembangunan, 2025)
This outreach program aims to raise awareness among the community, particularly PKK mothers, about the importance of creating smoke-free household areas to support family health and economic well-being. Smoke-free households are expected to reduce the harmful effects of smoking on family members’ health, especially children, and decrease household spending on tobacco products and healthcare costs. From an economic perspective, reducing tobacco consumption can improve household resource allocation for more productive needs and enhance the overall quality of family life. The method employed in this program is participatory, combining lectures, group discussions, and simple simulations on the economic impact of tobacco expenses. The sessions are conducted through a series of in-person meetings with PKK mothers. Each session includes presentations on the dangers of smoking, the economic consequences of smoking habits, and practical strategies for creating smoke-free household areas. The results of the program indicate an increased awareness among PKK mothers about the importance of smoke-free household areas and a deeper understanding of the economic implications of smoking in households. Additionally, there is a noticeable shift in household budget management, with a reduction in spending on tobacco products and a reallocation toward needs that better support the family’s health and well-being.